Evaluation of a COVID-19 IgM and IgG rapid test; an efficient tool for assessment of past exposure to SARS-CoV-2 - Hoffman, T.; Nissen, K.; Krambrich, J.; Rönnberg, B.; Akaberi, D.; Esmaeilzadeh, M.; Salaneck, E.; Lindahl, Johanna F.; Lundkvist, Å. (Informa UK Limited, 2020)
COVID-19 is the most rapidly growing pandemic in modern time, and the need for serological testing is most urgent. Although the diagnostics of acute patients by RT-PCR is both efficient and specific, we are also crucially in need of serological tools for investigating antibody responses and assessing individual and potential herd immunity. We evaluated a commercially available test developed for rapid (within 15 minutes) detection of SARS-CoV-2-specific IgM and IgG by 29 PCR-confirmed COVID-19 cases and 124 negative controls. The results revealed a sensitivity of 69% and 93.1% for IgM and IgG, respectively, based solely on PCR-positivity due to the absence of a serological gold standard. The assay specificities were shown to be 100% for IgM and 99.2% for IgG. This indicates that the test is suitable for assessing previous virus exposure, although negative results may be unreliable during the first weeks after infection. More detailed studies on antibody responses during and post infection are urgently needed.